FUNGSI LEGISLATIF DESA PASCA REFORMASI (TELAAH KRITIS ATAS UU NO. 22/1999 TENTANG PEMERINTAHAN DAERAH, UU NO. 32/2004 TENTANG PEMERINTAHAN DAERAH, DAN UU NO. 6/2014 TENTANG DESA) - Lutfy, Riza Multazam (Jurnal Yuridis, 2014)
This paper aims to determine the function of village legislative at post-reform. Based on historical data as well as critical analyzes of UU No. 22/1999 tentang Pemerintahan Daerah, UU No. 32/2004 tentang Pemerintahan Daerah, and UU No. 6/2014 tentang Desa, it can be concluded that the function of village legislative at post-reform is ups and downs. BPD 1999 has such a dominant function, so that the village government is unbalanced. The function of BPD 2004 is stripped down, so that the village executive can run his will without any supervision. The BPD 2014 is equipped with control function, so that the expected mechanism of checks and balances in village governance can be realized. Thus, it can be said that the function of BPD 1999 is dominant, the function of BPD 2004decreased, while the function of BPD 2014 is placed in a matched.